PERLINDUNGAN KONSUMEN TERHADAP PENGGUNAAN PLASTIK BERBAHAYA SEBAGAI KEMASAN PANGAN DALAM UPAYA MENINGKATKAN MINAT BELI - Zeshasina Rosha; Afriva Khaidir (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2019)
Plastic products contain ingredients that can harm human health, but these products are often used as food packaging. This article discusses the issue of consumer protection against the activities of businesses that use plastic products as food packaging and the government's role in supervising the use of plastic products for this purpose. This article is compiled based on juridical-normative literature studies, meaning that data is sourced from literature (secondary data) relating to consumer protection, both from the results of previous studies that are associated with statutory provisions. From the data analysis it can be concluded that businesses have violated the legal provisions of consumer protection because they use dangerous plastic products as food packaging. To minimize this adverse behavior, the government must provide information to consumers and businessman about the use of plastic packaging and supervise the use of plastic products by businessman. In addition, the government needs to require businesses to include symbols, triangle codes, and information on types of plastic used in places that are easily seen and read by consumers. Thus, consumers know clearly whether the plastic used is dangerous or harmless to package food products so that they make a decision to buy or not buy the intended product.